Building for the Future: Reflection, Resources, and Recommendations. Issue 168 (2nd December 2019) - Howard, Jimmy L.; Kerr, Kathleen G.
Abstract: We conclude the text with a look to the future and considerations and recommendations for centering social justice in residence life contexts.